2011
DOI: 10.1038/pj.2011.105
|View full text |Cite
|
Sign up to set email alerts
|

β-Sheet peptide-assisted polymerization of diacetylene at the air–water interface and thermochromic property

Abstract: A peptide-diacetylene hybrid (PDH), in which 5,7-dodecadiynedioic acid was conjugated to the amphiphilic penta-peptide Leu-Lys-Leu-Lys-Leu, which can form b-sheets on both ends of the diacetylene moiety, was prepared through solid-phase peptide synthesis using fluorenylmethoxycarbonyl chemistry. Spreading experiments and spectroscopic observations showed that the PDH formed a stable Langmuir monolayer, primarily in the parallel b-sheet conformation at the air-water interface. When the PDH monolayer was exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…The serial multi-chiral diacetylene (DA) monomers 1 possessing 2(5 H )-furanone structure were synthesized via the Glaser reaction [ 29 ] of N -[5-( S )-alkoxy-2(5 H )-furanonyl] amino acid propargyl esters 6 (Scheme S1, Supporting Information), [ 30,31 ] and systematically characterized by 1 H NMR, 13 C NMR, FTIR, UV, MS, and elemental analysis (see their data, especially their spectra and the discussion on the structural characterization of DA monomers 1 in the Supporting Information). DA monomers 1 are constructed from four parts, 2(5 H )-furanone, L -menthol, amino acid, and propargyl bromide, and the former three units may make 1 have multiple chiral centers (Scheme S1, Supporting Information), which can easily bring the novel chiral PDAs with tunable structure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The serial multi-chiral diacetylene (DA) monomers 1 possessing 2(5 H )-furanone structure were synthesized via the Glaser reaction [ 29 ] of N -[5-( S )-alkoxy-2(5 H )-furanonyl] amino acid propargyl esters 6 (Scheme S1, Supporting Information), [ 30,31 ] and systematically characterized by 1 H NMR, 13 C NMR, FTIR, UV, MS, and elemental analysis (see their data, especially their spectra and the discussion on the structural characterization of DA monomers 1 in the Supporting Information). DA monomers 1 are constructed from four parts, 2(5 H )-furanone, L -menthol, amino acid, and propargyl bromide, and the former three units may make 1 have multiple chiral centers (Scheme S1, Supporting Information), which can easily bring the novel chiral PDAs with tunable structure.…”
Section: Resultsmentioning
confidence: 99%
“…The DA monomers 1 were polymerized after their self‐assembly resulted from the hydrogen bonding between amine and carbonyl groups (Scheme ) during the preparation of DA vesicles (see Experimental Section, Supporting Information) . There are many poly­merization methods for the preparation of PDAs, and the common approach is the UV‐induced photo‐polymerization .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At a higher concentration (1.0 μM), the π– A isotherm curves of the binary systems were completely different from those of the sole DPPC membrane ( Figure 7 ). It has been reported that β-sheet peptides themselves form a monolayer at the air–water interface by compression [ 45 , 46 ]. π was already high at the start point of compression, which indicated that a large amount of EG n peptides might be present at the interface.…”
Section: Discussionmentioning
confidence: 99%